Endovascular Treatment of Posterior Circulation Saccular Aneurysms With the p64 Flow Modulation Device: Mid-and Long-Term Results in 54 Aneurysms From a Single Center - Hellstern, Victoria; Aguilar-Pérez, Marta; Henkes, Elina; Serna-Candel, Carmen; Wendl, Christina; Bäzner, Hansjörg; Ganslandt, Oliver; Henkes, Hans (Frontiers in Neurology, 2021)
Objective: Flow diverter (FD) stents have become one of the most common tools for treating intracranial aneurysms; however, their role in treating posterior circulation aneurysms is still discussed with controversy. In this study, we evaluated the safety and effectiveness of p64 FD for the treatment of saccular, unruptured aneurysms in the posterior circulation over a long-term follow-up period in a single center. Methods: From our prospectively maintained database, we retrospectively identified patients who underwent treatment of an intracranial saccular aneurysm arising from the posterior circulation with ≥1 p64 FD implanted or attempted between October 2012 and December 2019. Aneurysms could have been treated with prior or concomitant saccular treatment (e.g., coiling, intraaneurysmal flow diversion). Aneurysms with parent vessel implants other than p64, fusiform aneurysms, and dissections were excluded. Peri- and postprocedural complications, clinical outcome, and clinical and angiographic follow-up results were evaluated. Results: In total, 54 patients (45 female, 9 male; mean age 55.1 years) with 54 intracranial aneurysms met the inclusion criteria. In 51 cases (94.4%), one p64 was implanted; in 2 cases (3.7 %), two p64s were implanted; in one case, deployment of the p64 was not feasible. Procedural complications occurred in 3.7% and postprocedural complications in 9.3 %, respectively. Early, mid-term, and long-term angiographic follow-up examinations showed complete or near-complete aneurysm occlusion OKM C + D in 56%, 75.6 %, and 82.9 %, respectively. Asymptomatic side vessel occlusions occurred in 3.8%, each during first the first follow-up. Conclusions: The implantation of a p64 FD is a safe and effective device for endovascular treatment of posterior circulation saccular aneurysms with a high success rate and low morbi-mortality.